Efforts to Improve Clean and Healthy Living Behavior (PHBS) at the IMBS Miftahul Ulum Pekajangan Pekalongan Islamic Boarding School - Rr. Vita Nurlatif; Mega Prima Nur Fajri; Yasinta Maria Yosephine; Zubaidah Tsania Ulul Azmi; Putri Rika Amalia; Novalista Ananda Putri; Aisha Laura Devi; Chairiza Paundrian Negari (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
A healthy lifestyle is the effort of everyone who wants to always be healthy, namely by paying attention to a healthy lifestyle so that the body always avoids various diseases. This research aims to increase the understanding and knowledge of adolescent students about Clean and Healthy Living Behavior (PHBS) at the IMBS Miftahul Ulum Pekajangan Islamic Boarding School through a series of intervention programs, involving 50 adolescent students including first aid socialization, reproductive health, mental health, and environmental health. It can be concluded that this activity succeeded in increasing the awareness and skills of students, with positive feedback and a real action plan to implement PHBS in the pesantren environment.